Assessment of point-of-care quantitative serum canine pancreatic lipase testing for diagnosing acute pancreatitis in dogs - Liu, Pin-Chen; Teng, Kendy Tzu-yun; Lin, Tsia-Lu; Sung, Chi-Hsuan; Cheng, Tsun-Li; Chou, Chi-Chung (Frontiers in Veterinary Science, 2025)
IntroductionCurrent point-of-care testing for canine-specific pancreatic lipase (CPL) provides semi-quantitative measurements with binary results. Recently, a commercial point-of-care testing method (Vcheck CPL) that offers quantitative measurement of CPL has emerged. However, clinical studies on its value (or utility) are limited. Therefore, this study aimed to evaluate the clinical utility of this commercial point-of-care CPL in diagnosing dogs with suspected acute pancreatitis and to assess its correlation with a commercial semi-quantitative test and other clinicopathological variables.MethodsA prospective observational study included 33 dogs with suspected acute pancreatitis and 20 clinically healthy dogs. Serum Vcheck CPL and SNAP ® cPL were tested, and clinical consensus scores were determined by 5 internists. Eleven dogs with suspected acute pancreatitis underwent follow-up testing during hospitalization. The intra-class correlation coefficient (ICC) was used for statistical analysis to assess the agreement between assays and the internists’ consensus score.ResultsDogs with suspected acute pancreatitis had significantly higher serum Vcheck CPL (median: 843 μg/L, range: 77–2001, p < 0.0001) than healthy control dogs (median: 94 μg/L, range: 49–294). By day 3 of hospitalization, serum Vcheck CPL had significantly decreased in dogs with suspected acute pancreatitis compared to day 1. The ICC score between the clinical consensus score, Vcheck CPL, and SNAP ® cPL was 0.75, indicating good agreement. Serum Vcheck CPL concentration was significantly correlated with serum concentrations of amylase, lipase, creatinine, ALP, and CRP.DiscussionThis study found good agreement between Vcheck CPL and SNAP ® cPL. This quantitative Vcheck CPL testing could serve as an adjunctive tool in diagnosing dogs with acute pancreatitis.